Genetic diversity and population structure of malaria vector mosquitoes Anopheles subpictus, Anopheles peditaeniatus, and Anopheles vagus in fve districts of Sri Lanka - Weeraratne, T.C.; Surendran, S.N.; Walton, C.; Karunaratne, S.H.P.P. (University of Jaffna, 2018)
: Although Sri Lanka is considered as a malaria-free nation, the threat of re-emergence of outbreaks still remains due to the high prevalence and abundance of malaria vectors. Analysis of population genetic structure of malaria vectors is considered to be one of the vital components in implementing successful vector control pro grammes. The present study was conducted to determine the population genetic structure of three abundant malaria vectors; Anopheles subpictus sensu lato (s.l.), Anopheles peditaneatus and Anopheles vagus from fve administrative districts in two climatic zones; intermediate zone (Badulla and Kurunegala districts) and dry zone (Ampara, Batticoloa and Jafna districts) of Sri Lanka using the mitochondrial gene, cytochrome c oxidase subunit I (COI)
Keywords: anopheles subpictus; anopheles peditaeniatus; anopheles vagus; population genetic structure; COI; sri lanka